Peer-to-Peer Video The Economics, Policy, and Culture of Today's New Mass Medium - Noam, Eli M.; Pupillo, Lorenzo Maria (Springer New York : Imprint: Springer, 2008)
Peer-to-Peer (P2P) is a communication structure in which individuals interact directly, without going through a centralized system. The implications of this architecture go far beyond the technological realm; the ability of individuals to share digital content files, including audio and video material, in real time, facilitates communication and, at a deeper cultural level, promotes community without hierarchy or strict control. As Eli Noam, Lorenzo Pupillo, and their colleagues demonstrate in this timely and incisive volume, P2P has permeated all facets of society, from YouTube and music downloading experiments on college campuses to international policy debates over intellectual property rights. Peer-to-Peer Video is the first book to apply economic principles to analyze and understand the P2P phenomenon, considering such topics as "consumer demand and the commons" and "file sharing and the copyright crisis." Moreover, the authors, who include scholars, consultants, and industry executives, provide numerous contemporary examples from the U.S. and around the world to shed light on P2P as a mass medium, exploring such issues as pricing, licensing, security, and regulation. The result is provocative commentary on a slice of popular culture that will interest scholars and students, policymakers, media industry professionals, and general readers alike.